2019
DOI: 10.22452/mojem/vol7no2.4
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF LECTURER’S TRANSFORMATIONAL LEADERSHIP ON STUDENTS’ EMPLOYABILITY: MALAYSIAN TECHNICAL AND VOCATIONAL EDUCATION & TRAINING INSTITUTIONS

Abstract: As the economy of Malaysian government has transformed from a typical economy to human capital economy, the demand for Technical and Vocational Education & Training (TVET) institutions as a platform to develop human capital is also increasing. TVET based institutions in Malaysia are known as formal and informal learning sector which provide youthful people with the expertise and skills needed in the work sector. However, TVETbased qualifications and careers in Malaysia are perceived poorly and does not receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…This is consistent with studies conducted by researchers that transformational leadership influences employability (e.g. Omar, Zulazmi, & Ladin, 2019;Peng, Sheng-Hwa, & Han-Yu, 2018;Yizhong et al, 2018), innovative behavior (e.g. Rassa & Emeagwali, 2020;Adam, Indradewa, & Shah, 2020;Widodo & Mawarto, 2020), and job involvement (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with studies conducted by researchers that transformational leadership influences employability (e.g. Omar, Zulazmi, & Ladin, 2019;Peng, Sheng-Hwa, & Han-Yu, 2018;Yizhong et al, 2018), innovative behavior (e.g. Rassa & Emeagwali, 2020;Adam, Indradewa, & Shah, 2020;Widodo & Mawarto, 2020), and job involvement (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…It can be concluded that this kind of leadership style is not the main leadership style applied by the lecturers. In essence, this result is aligned with a past research by Omar et al (2019) which found that the level of transformational leadership practice among TVET institutions' lecturers are just in a moderate application. This finding supports Ahmad (2015) statement, who stated that transformational leadership is less practiced in TVET context probably because TVET lecturers are more inclined to practice other leadership approaches that are more concerned with complete control by the leader while conducting teaching and learning.…”
Section: Discussionsupporting
confidence: 87%
“…and high reliability (Kenayathulla, Ling, Razak, & Darusalam, 2019;Omar, Zulazmi, & Ladin, 2019) of the scale. Secondly, this study established validity considering three validity strategies: content, construct, and criterion validity respectively.…”
Section: Malaysian Online Journal Of Educational Management (Mojem)mentioning
confidence: 95%